The Physical Capacity of Rowing Athletes Cannot Reverse the Influence of Age on Heart Rate Variability during Orthostatic Stress - RODRIGUES,GABRIEL D. (2021)
Abstract The current study was undertaken to test the hypothesis that the high physical capacity of rowing athletes may not reverse the influence of age on cardiac autonomic control decline estimated by heart rate variability (HRV). Forty-four male subjects divided in four groups: 11 young athletes (YA; 18 ±1 year), 11 young non-athletes (YNA; 20 ±1 year), 11 middle age athletes (MAA; 43 ±6 years) and 11 middle age non-athletes (MNA; 44 ±8 years) participated in the study. Heart rate (HR) was recorded beat-by-beat for 10 minutes in supine (SUP) and 10 min in orthostatic (ORT) positions. HRV was analyzed in the frequency domain to obtain the spectral power in the high (HF) and low frequency (LF) bands, and the changes to ORT (%∆HRV) were calculated (ORT – SUP / SUP). During SUP, HF was lower in MNA and MA compared to YA and YNA, while LF was lower in MNA than YA. For %ΔHRV, %ΔHF was higher in YA than YNA, MA and MNA. The %ΔLF was not different among groups. In conclusion, aging seems to overcome the influence of physical fitness on neural regulation of the heart, as highlighted by the HRV response to active standing.